The Options and Limitations of the Brain Fingerprinting Lie Detection Method in the Criminal Proceeding1 - Budaházi, Árpád; Fantoly, Zsanett; Kakuszi, Brigitta; Bitter, István; Czobor, Pál (Magyar Rendészet, 2019)
The aim of this study is to introduce the new lie detection method of brain fingerprinting already introduced in the United States of America. According to some scholars, the method of a brain-focused instrumental credibility examination of testimonies still unknown in Hungary is highly reliable, establishing their concept on their belief that the human brain does not lie. First of all, we shall examine the possibilities lying in the measure, and second of all, we shall introduce the doubts causing the delay of its admission in Hungary.